The Effect of Affiliate Marketing Attractiveness on Impulse Buying: A Study on Tiktok Shop In Generation Z - Imam Gozali; Bela Ayu Saputri (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study investigates the effects of affiliate marketing Attractiveness and flash sale promotions on impulse buying behavior among Generation Z users of TikTok Shop. Aquantitative research design was employed, utilizing a non-probability convenience sampling technique to recruit respondents from the target population. Data were collected through a structured questionnaire that had met the required validity and reliability standards. The collected data were analyzed using multiple linear regression with the assistance of SPSS version 25. The findings reveal that affiliate marketing Attractiveness exerts a positive and statistically significant effect on impulse buying. Likewise, flash sale promotions significantly stimulate consumers' impulsive purchasing behavior. These results highlight the strategic importance of leveraging credible and engaging affiliates alongside time-limited promotional campaigns to encourage spontaneous purchasing decisions among Generation Z consumers within the TikTok Shop ecosystem.